Using Debate to Enhance Students’ Speaking Ability As Their Character Building - Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2017)
The goal of language learning is to communicate. Therefore, it will be useless for a language learner who cannot use the language at the end of the study. As one of English skills to learn, speaking stands as an important aspect to be learned. It has been taught since the elementary schools, even now kindergarten and playgroup. Instead of getting more students who are able to speak fluently in English, the outcome seems not to be satisfied. For instance, it can be inferred that from a hundred of students, only one who is able to speak fluently in English. The methods and techniques conducted by the teachers in the learning and teaching process are considered as one of factors. In terms of conducting an alternative technique to enhance the speaking skills of the students, here is debate. In this cooperative learning method, as where this can be included, the students are encouraged to play their own roles in teaching and learning process. Through Debate as a technique, the students are expected to be more confident in delivering their own point of view in many issues in whatever circumstances. The character building can be considered as building confidence or mental aspects of the students. Whoever is it, they can freely show off in a more global situation, as example, which needs a skill of excellent public speaking. This article will describe the steps of debate in order to improve the student’s speaking skill. Chronologically, the subtopics to discuss are: teaching speaking, which contains the principles of teaching speaking in English, debate in language teaching, contains the principles of debate used in language teaching-learning process, and the teaching procedures, which will discuss how it is conducted procedurally in the classroom.